Diversité Des Loranthaceae Et Leur Impact Sur Vitellaria Paradoxa C.F.Gaertn.: Un Fruitier À Grande Valeur Socio-Économique Au Nord-Bénin - Ahamidé, Innocent D. Y.; Tossou, Monique G.; Yédomonhan, Hounnankpon; Adomou, Aristide C.; Houénon, Janvier; Akoègninou, Akpovi (European Scientific Journal, ESJ, 2017)
Shea butter: Vitellaria paradoxa C. F. Gaertn (Sapotaceae) is a fruit tree in the Sudano-Sahelian region where it is a major economic source. Unfortunately, in Benin, the species has been revealed in recent decades, the target of parasitic vascular plants of Loranthaceae family that threaten its conservation. The present study, carried out in northern Benin, evaluated the impact of these parasitic plants on the shea of two phytogeographical zones. The botanical inventory identified three species of Loranthaceae in fields and protected areas. The rate of infestation and parasite density were assessed and their variation on shea was assessed. The results show that shea is parasitized by three species of Loranthaceae in varying proportions: Agelanthus dodoneifolius (DC.) Polh. and Wiens (191.75 tufts / ha), Tapinanthus globiferus (A. Rich.) Van Tieghem (70.57 tufts / ha) and T. Ophiodes (Sprague) (2 tufts / ha). The impact of Loranthaceae on shea productivity varies significantly between fields and protected areas with infestation rates of 87% versus 42% and average densities per shea foot of 14.76 tufts versus 3.62 tufts. These results are data to be taken into account in the control programs against Loranthaceae which parasitize shea.